Analisis Tingkat Kepuasan Pasien Atas Pelayanan Zaal Kebidanan dan Kandungan pada RSUD Hamba Muara Bulian - Ratna Ratna; Nadiatul Khoiroh (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
One of the targets of Obstetrics and Gynecology at the general hospital of bulian estuary, namely increasing the level of patient satisfaction so that this becomes one of the indicators for measuring service quality. One of the main elements supporting the level of patient satisfaction is patients with their resources. The purpose of the study was to determine the level of patient satisfaction with the quality of care in obstetrics and gynecology at the general hospital of bulian estuary. Respondents were patients with obstetrics and gynecology at 75 general hospitals in the bulian estuary servants. Methods of collecting data using questionnaires, observation, documentation. To test the hypothesis, the technique used is path analysis. Research results: (1) the quality of services in obstetrics and gynecology is very good, (2) the level of patient satisfaction with obstetrics and gynecology is very good. Advice for obstetrics and gynecology public hospitals in bulian estuary servans must improve service quality and maintain then maintain existing quality must be done, so that customers or users of the hospital do not feel disappointed and the service users do not move elsewhere.